Safety evaluation of AB-LIFE® (Lactobacillus plantarum CECT 7527, 7528 and 7529): Antibiotic resistance and 90-day repeated-dose study in rats. (June 2016) - Mukerji, Pushkor; Roper, Jason M.; Stahl, Buffy; Smith, Amy B.; Burns, Frank; Rae, Jessica Caverly; Yeung, Nicolas; Lyra, Anna; Svärd, Laura; Saarinen, Markku T.; Alhoniemi, Esa; Ibarra, Alvin; et al.
Abstract: AB-LIFE ® is a probiotic product consisting of equal parts of three strains of Lactobacillus plantarum (CECT 7527, 7528, and 7529) blended with inert excipients. Whole genome sequencing was performed on each of the three strains. Antibiotic resistance was evaluated by genomic mining for resistance genes, and assessment for transferability. No risk of transfer potential was identified for any antibiotic resistance genes in the three strains. AB-LIFE ® was evaluated for potential subchronic oral toxicity in rats, with dosages of 300 and 1000 mg/kg BW/day (equivalent to 5.55 × 10 10 and 1.85 × 10 11 CFU/kg BW/day). Survival of the three test strains through the gastrointestinal tract was supported by fecal analysis. No adverse effects were identified with respect to in-life parameters, clinical or anatomic pathology, translocation, or fecal chemical analyses. The no-observed-adverse-effect level (NOAEL) for AB-LIFE ® in male and female rats was 1000 mg/kg BW/day (1.85 × 10 11 CFU of AB-LIFE ® /kg BW/day), the highest dose level evaluated. These results, in conjunction with a previous acute toxicity study in rats, support the conclusion that AB-LIFE ® is safe for human consumption. Highlights: L. plantarum strains CECT 7527, 7528 and 7529 survive GI tract conditions in vivo . The subchronic NOAEL for AB-LIFE ® L. plantarum strains (CECT 7527, 7528 and 7529) is 1000 mg/kg/day. AB-LIFE ® administration does not present a risk for systemic translocation. AB-LIFE ® administration does not present a risk for transfer of antibiotic resistance.